PENGEMBANGAN MEDIA PEMBELAJARAN GAME EDUKASI BERBASIS ANDROID PADA MATERI PANCA INDERA KELAS IV SDN I TAWING - Vika Ayundasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on the results of observations and interviews that students experience difficulties in understanding the five senses material because learning activities are still monotonous, and the use of learning media that uses technology is not yet optimal. Teachers are still focused on print media such as books during the learning process. To provide this solution, researchers developed Android-based educational game learning media that can be accessed by teachers and students at any time.This research uses Research and Development (R&D) research. The development model is ADDIE. The stages are 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The data collection techniques used were interviews and questionnaires. Data analysis techniques are obtained from the results of expert validity tests, teacher and student practicality tests, as well as effectiveness tests obtained from student post-test results. The validity results from material experts obtained a score of 86% and the validity results of the Android-Based Educational Game Learning media from media experts obtained a score of 92.3% in the very valid/suitable for use category. For the practicality test the teacher got a score of 96% and the students 98.5% in the very practical category, and for the effectiveness test in the broad test they got a score of 95% in the very effective category.